Treatment for landfill leachate via physicochemical approaches : an overview - Khoo, Kuan Shiong (Array, 2020)
Leachate waste consists of various mixtures of organic, inorganic, and heavy metal contaminants, which are responsible for groundwater and surface water contamination. Landfills apply physical, chemical, and biological processes for the treatment of leachate. Most studies on leachate treatment by coagulation and flocculation are based on the selection and performance of natural based biopolymers in comparison with various inorganic metal salts and grafted polymers used for the removal of contaminants. In addition, adsorption processes utilizing non-conventional activated carbons as absorbents are the current emerging focus of the researchers in leachate treatment. These adsorbents are low-in-cost, efficient, and renewable compared to conventional adsorbents. The present paper aimed to evaluate and review the technology utilising various greener approaches in coagulation, flocculation, and adsorption as the physicochemical approaches to leachate treatment. The challenges and future work regarding the development of these green products in the commercial markets were comprehensively evaluated.